2015
DOI: 10.1186/s40064-015-1041-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of training in hypoxia on repeated sprint performance in female athletes

Abstract: BackgroundThis study determined the effect of repeated sprint training in hypoxia (RSH) in female athletes.MethodsThirty-two college female athletes performed repeated cycling sprints of two sets of 10 × 7-s sprints with a 30-s rest between sprints twice per week for 4 weeks under either normoxic conditions (RSN group; FiO2, 20.9%; n = 16) or hypoxic conditions (RSH group; FiO2, 14.5%; n = 16). The repeated sprint ability (10 × 7-s sprints) and maximal oxygen uptake () were determined before and after the trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
52
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 30 publications
4
52
0
2
Order By: Relevance
“…In addition, a significant increase in peak power output during the RSA test (5 × 6-s maximal sprint) was observed only in the HYPO group. These findings are consistent with a recent publication that reported a significant improvement in 7-s maximal sprint performance after four weeks of RSH in female team-sport athletes [25]. Moreover, we recently demonstrated that 6 successive days of RSH significantly improved the running time of the initial phase of 60-m sprint, with a concomitant increase in muscle PCr content, although the sample size was relatively small [26].…”
Section: Performance Adaptationssupporting
confidence: 92%
See 2 more Smart Citations
“…In addition, a significant increase in peak power output during the RSA test (5 × 6-s maximal sprint) was observed only in the HYPO group. These findings are consistent with a recent publication that reported a significant improvement in 7-s maximal sprint performance after four weeks of RSH in female team-sport athletes [25]. Moreover, we recently demonstrated that 6 successive days of RSH significantly improved the running time of the initial phase of 60-m sprint, with a concomitant increase in muscle PCr content, although the sample size was relatively small [26].…”
Section: Performance Adaptationssupporting
confidence: 92%
“…Moreover, Hamlin et al [21] found that RSA (8 × 20-m sprint with 20-s rest between sprints) was significantly improved following 3 weeks of RSH among rugby players. We also reported previously that 4 weeks of RSH (two successive sets of 10 × 7-s sprints with 30-s rest periods between sprints, F i O 2 , 14.5 %) led to a 3-fold increase in initial sprint power output during a repeated sprint test (10 × 7-s sprints) compared with the same training in normoxia [25]. The enhanced RSA may be explained by augmented adenosine triphosphate (ATP) production via ATP-phosphocreatine (ATP-PCr) and glycolytic systems, as well as the aerobic energy system.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…In recent years, all‐out SIT under hypoxic condition has been reported to induce greater improvements in exercise performance compared with that under normoxic condition. Recent studies have shown greater improvement in power output during repeated sprint test following SIT under hypoxia compared with that under normoxia in male sprinters (Kasai et al ) and female lacrosse athletes (Kasai et al ). In addition, SIT under hypoxia leads to greater increases in power output and number of sprint sets until exhaustion during repeated sprint tests in male cyclists (Faiss et al ) and male and female cross‐country skiers (Faiss et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Hypoxic exposure increases the contribution of the anaerobic energy system during all‐out sprint exercise (Ogura et al ). Therefore, researchers speculate that the increased stimulus to the anaerobic energy system may contribute to greater improvements in anaerobic exercise performance (Kasai et al ). If the alteration in the energy system contributions during SIT due to the change in oxygen concentration affects the SIT‐induced performance adaptations, all‐out SIT under hyperoxia may cause greater SIT‐induced improvement in aerobic exercise performance because hyperoxia exposure increases the percentage of energy supplied from the aerobic system during maximal exercise (Linossier et al ).…”
Section: Introductionmentioning
confidence: 99%